Home Groups: Integrating Peer Support and Clinical Care in a Community Mental Health Center. Issue 2 (3rd April 2019) - Styron, Thomas; Pavlo, Anthony; Miller, Rebecca; Kamens, Sarah; Cooley Hall, Benjamin; Fortgang, Rebecca; Ivey, Alexandra; Edwards, Maria; Youins, Richard; Bellamy, Chyrell; Davidson, Larry
ABSTRACT: With peer supporters now comprising one of the most rapidly growing components of the mental health workforce, group interventions that combine their expertise with those of more traditional mental health providers are needed. An example of one such intervention, developed and implemented at a large community mental health center for individuals with serious mental illnesses, is presented. Called a "Home Group" and co-led by peers and clinical psychology interns, this intervention provides unique learning opportunities for peers and trainees and many potential benefits to group members. Vignettes to illustrate the model are presented and the potential therapeutic and empowering aspects of this innovative and promising approach are identified and discussed.